2013
DOI: 10.1002/ar.22823
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐127 is Downregulated by Tudor‐SN Protein and Contributes to Metastasis and Proliferation in Breast Cancer Cell Line MDA‐MB‐231

Abstract: Tudor-SN is a multifunctional protein that is highly expressed in multiple cancers including breast cancer. Tudor-SN, as a component in RNA-induced splicing complex, was recently reported to regulate gene expression in a micro-RNA (miRNA)-dependent manner, such as let-7, miR-34a and miR-221. However, how Tudor-SN is associated with cancer development still remains largely elusive. In the present study, we explored the role of Tudor-SN in breast cancer. Stable knockdown of endogenous Tudor-SN, performed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…In breast cancer cell lines, Wu et al (36) suggested that miR-339-5p may inhibit the expression of BCL6 mRNA, which was associated with suppressed migration and invasion of cells. Zhao et al (37) identified that the downregulation of miR-127 expression may promote metastasis and proliferation, and that BCL6 was a target of miR-127. Pinto et al (38) demonstrated that, in metastatic lymph nodes, the expression of BCL6 protein was significantly lower compared with that in the corresponding primary breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cell lines, Wu et al (36) suggested that miR-339-5p may inhibit the expression of BCL6 mRNA, which was associated with suppressed migration and invasion of cells. Zhao et al (37) identified that the downregulation of miR-127 expression may promote metastasis and proliferation, and that BCL6 was a target of miR-127. Pinto et al (38) demonstrated that, in metastatic lymph nodes, the expression of BCL6 protein was significantly lower compared with that in the corresponding primary breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tudor-SN is a type of multi-functional protein that is widely expressed in tumor cells. Tudor-SN has the ability to activate various transcription factors, including NF-κB, and is involved in adjusting the expression of miRNAs (11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that Tudor-SN has a close association with lipid metabolism, and that the expression of lipoprotein in liver cells can be affected through adjustment of lipid metabolism-associated genes (11,12). Inactivation of alkylglycerone phosphate synthase (AGPS) can lower the ether ester level in the tumor cell and cancer pathogenicity, while overexpression of AGPS can increase the ether ester level, viability and migration potential of various tumor cells, including 231MFP, C8161 melanoma, PC3 prostate cancer and primary breast cancer cells, and advance the growth and migration of the tumor cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of its link to cancer progression, Tudor-SN has been shown to promote resistance to apoptosis and to be induced by NF-κB, which as mentioned above, was increased in the CD-induced tissues through potentially decreased miR-146a and 146b expression (Figure 5) [45, 49]. Amongst the miRNAs influenced by Tudor-SN, is miR-127, and studies have shown that Tudor-SN triggers miR-127 downregulation in breast cancer cells [50]. Our western blot results illustrate that Tudor-SN was significantly increased in the CD-induced tissues (Figure 6).…”
Section: Discussionmentioning
confidence: 99%